Laparoscopic atypical gastrectomy - Haro, Camila; Muniz, Nicolás; González, Nicolás; ´Pouy, Andrés; Cubas, Santiago (Cirugía del Uruguay, 2021)
Gastric cancer is the fifth most frequent malignant neoplasm worldwide and in our country, and the fourth cause of cancer mortality. The survival rate continues to be low, since its diagnosis is usually late and in advanced stages. In countries with a high incidence, endoscopic screening is performed, making the diagnosis in early stages, with a better prognosis. In these patients there is a lower risk of regional or distant spread, and tailored treatments can be considered, avoiding wide resections.